Radiology - Shaw, Ashley ((Clinical cases uncovered), 2009)
From choosing the relevant investigation through to interpretation and its effects on patient management, Radiology: Clinical Cases Uncovered provides an overview of the modern imaging department, including radiation and safety considerations, putting radiology in its clinical context.The cases, covering a broad spectrum of disease processes in all body systems, are illustrated with over 250 high-quality images, while the extensive self-assessment section and accompanying explanatory notes consolidates learning and provides invaluable examination practice.Radiology: Clinical Cases Uncovered is perfect for medical students, Foundation doctors and radiographers.